Influences of Tidal Flat and Thermal Discharge on Heat Dynamics in Xiangshan Bay - Kong, Gaoqiang; Li, Li; Guan, Weibing (Frontiers in Marine Science, 2022)
Water temperature in estuaries is sensitive to thermal discharges and expansive tidal flats; as such, this parameter is essential in maintaining estuarine ecosystem. Semi-enclosed water bodies with poor water exchange easily accumulate heat. This is especially true for Xiangshan Bay, which contains two power plants and a large area of tidal flats. This bay was used as an example to study water temperature and heat dynamics, considering the thermal discharge and tidal flats. This study developed and validated a three-dimensional hydro-heat flux numerical model using field data on tidal elevation, currents, water temperature, and tidal flat temperature. The Finite Volume Community Ocean Model combines an accurate thermal discharge model with the air-water-tidal flat heat flux model. The findings showed that thermal discharge provides heat to the bay in summer and winter, and increases the water temperature of the entire bay by 0.7°C in summer, while maintaining water temperature at 0.52°C in winter. The atmosphere and open seas had greater impacts on heat in the bay in winter and summer. The atmosphere and tidal flats provided heat to the bay in summer and absorbed heat from the bay during winter; the opposite was true for the open sea. The effect of tidal flats in summer is less than that in winter, and provides 1.31 × 1013 J of heat to the bay in summer, while taking 8.63 × 1013 J of heat from the bay in winter. This study provides a comprehensive understanding of the effects of tidal flats and thermal discharge on water temperature and heat in macro-tidal bays and estuaries; its results are applicable to similar bays around the world.